SIFAT TARIK DAN SIFAT LENTUR PADA BODY MOTOR KOMPOSIT LAMINA DENGAN PERLAKUAN ALKALI - Kevin Hanada; Sofyan Djamil; Sobron Yamin Lubis (Jurnal Ilmiah Teknik Mesin POROS, 2021)
Composite is a combination of two or more materials that have different mechanical propertiesand characteristics. One of the reinforcement materials or reinforcement that is widely used is naturalmaterials. One of Indonesia's natural materials and a very large source of bamboo is widely used inbuilding construction as an alternative to wood because it has high flexibility and strength. To balancethe strength of bamboo with high tensile strength while low flexural strength, a solution is needed tomaximize the strength of bamboo by combining it with a bamboo composite system. In this study, bamboothat has been processed into woven sheets manually with plain weave type is then given a certain amountof epoxy resin and then a Tensile Strength Test is carried out using ASTM D3039 / D3039M and aflexural test using ASTM D7264 / 7264M to obtain maximum composite and flexural strength. After thetest was carried out, it was continued by observing the microstructure of the specimen using SEM(Scanning Electron Microscope). The results showed the tensile test value with a value of 50 Mpacompared to the ABS tensile strength value of 53 Mpa, the Modulus of Elasticity with a value of 0.38 GPacompared to the ABS modulus of elasticity of 0.41 Gpa. The results of the flexural test obtained flexuralstrength with a value of 47.06 Mpa compared to the value of ABS flexural strength of 49.6 Mpa, flexuralmodulus with a value of 0.52 Gpa compared to the value of ABS flexural modulus of 0.55 Gpa.